2008
DOI: 10.4141/s06-059
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of organic carbon in the stable soil humic fractions as affected by tillage management

Abstract: Murage, E. W. and Voroney, P. 2008. Distribution of organic carbon in the stable soil humic fractions as affected by tillage management. Can. J. Soil Sci. 88: 99Á106. Soil humus comprises a large and stable pool of soil organic matter (SOM); hence a better understanding of the fate of C in soil humic fractions can provide valuable information for the development of alternative tillage practices that will lead to long-term soil C sequestration. We used d 13 C techniques to investigate the effects of tillage on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
9
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 25 publications
3
9
1
Order By: Relevance
“…This stabilization, along with the incorporation of more plant residues, could help increase the soil organic C stock, and moreover, contributing agro-environmental benefits, such as increased soil fertility, erosion prevention, etc. These results coincide with those of other authors concerning the positive effect of no-tillage management on the increase in stable soil humic fractions content (Murage and Voroney, 2008), and on the contrary, its decrease under continuous tillage despite their intrinsic chemical recalcitrance (Bongiovanni and Lobartini, 2006).…”
Section: Soil Organic Matter Fractionationsupporting
confidence: 94%
“…This stabilization, along with the incorporation of more plant residues, could help increase the soil organic C stock, and moreover, contributing agro-environmental benefits, such as increased soil fertility, erosion prevention, etc. These results coincide with those of other authors concerning the positive effect of no-tillage management on the increase in stable soil humic fractions content (Murage and Voroney, 2008), and on the contrary, its decrease under continuous tillage despite their intrinsic chemical recalcitrance (Bongiovanni and Lobartini, 2006).…”
Section: Soil Organic Matter Fractionationsupporting
confidence: 94%
“…Different SOC fractions transformed each other, part of active SOC emissions of CO 2 , and part of it transformed into the steady-state SOC. A similar study of Murage and Voroney (2008) reported that PT was favoring to decompose crop residues into structural organic carbon (slow SOC). Therefore, it was the reason why slow SOC in PT is greater than NT and DL.…”
mentioning
confidence: 87%
“…Murage and Voroney (2008) reported tillage eff ects on the dynamics of native C (C3-C) and corn-derived C (C4-C) in fulvic acid (FA), humic acid (HA), and humin fractions:…”
Section: Soil Carbon Nitrogen and Nutrient Cyclingmentioning
confidence: 99%